Learning motivation of older adolescents in different educational environments - M.G. Nikitskaya; N.N. Tolstykh (Психологическая наука и образование)
Context and relevance. Learning motivation is the most important component of educational activity. The specification of educational motivation in different educational environments representing the modern context of secondary education in Russia should be based both on understanding of the processes of student's personal development and on the knowledge of the specifics of each educational environment. Objective. To analyze the specifics of educational motivation in the context of the personal development of older adolescents studying in three different educational environments (grades 10-11 of a regular secondary school and two colleges with different levels of entrance tests and academic performance requirements for applicants). Hypothesis. There are significant differences in the nature of students' learning motivation in three different educational environments, in the place of this motivation in the general structure of the motivation-need sphere of their personality and in a number of other personal characteristics of these adolescents. Methods and materials. The study involved 342 16–18-year-old adolescents studying in three different educational environments. The following research methods were used: the Method of Motivational Induction (MMI) by J. Nuttin, "Academic Motivation Scale for Schoolchildren" (AMS-S) created by T.O. Gordeeva et al., the questionnaire "Achievement Goal Questionnaire" (AGQ) – the Russian version of the questionnaire by E. Elliott et al. (M.G. Nikitskaya, I.L. Uglanova), "Satisfaction with Life Scale" (SWLS) by E. Diener adapted by E.N. Osin and D.A. Leontiev. Results. Statistically significant differences were revealed between the groups of adolescents studying in three educational environments in terms of the content of learning motivation and learning achievement goals, in the place of learning motivation in motivation-need sphere of adolescents, as well as in the relation of learning motivation to life satisfaction. Conclusions. The results may be used to improve the quality of education and upbringing of adolescents in schools and colleges of Russia with different contingent of students and various professional training programs.